Review of the STOL channel-wing aircraft design and development - Abdul Hamid, Mohd Faisal; Gires, Ezanee; Abu Talib, Abd Rahim; Surtan @ John, Meriwon (Aerospace Society Malaysia, 2024)
Custer channel wings, sometimes referred to as channel wings, have become a viable solution to control aerodynamic flow and enhance air vehicle performance. This design breakthrough, which dates back to the 1920s, involves redefining the traditional wing shapes into semi-circular or U-shaped configurations to promote suction effect that improves lift generation. Although channel wings present an exciting opportunity to transform the aircraft design, there are still unanswered questions, especially on the best way to integrate them into the contemporary aircraft. In order to fill these gaps, this study examines the viability of channel wing technology and evaluates its possible effects on the operation and design of the commercial aircraft. Through the new developments in materials science and engine technology, previous limitations related to the channel wing designs including weight penalties and drag inefficiencies can be overcome.